Dead Reckoning : Memories of the 1971 Bangladesh War - Boss, Sermila (Karachi Oxford University Press, 2011)
First Book of the war about the 1971 Pakistan between India.And the memories of warrior of this war. and also describe the detail of war.
Includes Bibliography, Notes and Index.
Originally Published in Great Britain in 2011.
Keywords: Interviews -- Collective Memory -- Social Aspects -- War Victims -- War and Society